Antonia Pozzi, Morte de uma estação: critica produttiva di alcune traduzioni in lingua portoghese - Milani, Ada (L'ospite ingrato, 2024)
This work intends to make a reflection on the translation of Antonia Pozzi’s lyrics into Portuguese. The first part of the study aims to offer a brief summary of the troubled editorial case of Parole (1939) and of the critical success of Pozzi’s poetry, relegated to the margins of the Italian literary canon for much of the twentieth century and «rediscovered» in recent decades also thanks to dissemination outside national borders. In the second part, some translations contained in Morte de uma estação (2012), the only collection in Portuguese dedicated to the poet, are analyzed: moving from Antoine Berman’s «analytic of translation», we question the translation choices, highlighting the deforming tendencies.